THE RELATIONSHIP BETWEEN FIFTH GRADE STUDENTS’ NUMBER SENSE AND THEIR MATHEMATICAL PROBLEM SOLVING - Mutmainnah, Annisa; Putra, Zetra Hainul; Syahrilfuddin, Syahrilfuddin (Institut Keguruan dan Ilmu Pendidikan Siliwangi, 2021)
This research was aimed to find out the relationship between the fifth grade students’ number sense and their mathematical problem solving. The participants of this study were 73 fifth grade students from a private Islamic school in Pekanbaru, Indonesia. The research method used is in the form of quantitative methods. The instrument in this study is a test, where the data collected by distributing a test about students’ number sense and their mathematical problem solving. Number sense indicators consist of number concepts, multiple representations, effects of operations, equivalent expressions, and computing and counting strategies. The problem solving materials consist of numbers, fractions, geometry, and measurements. The data analysis technique is done by presenting data, normality test, linearity test, linear regression test, and hypothesis testing using the Pearson product moment correlation. The results showed that there was a significant correlation between students’ number sense and their mathematical problem solving. After that, a correlation test is performed between all number sense indicators with mathematical problem solving materials. The indicator of computing and counting strategies has high correlation with measurement.